Penumbra : poems - Shewmaker, Michael (Athens, Ohio : Ohio University Press, 2017)
Penumbra-Michael Shewmaker's debut collection-explores the half-shadows of a world torn between faith and doubt.
The Seven ThundersAdvent; Destin Wedding; The Pastor; Übermensch; The Mime of Thermopylae; The Cooling Pond; Photo Found on a Dead Man's Phone; The End of the Sermon.
Print version record.
eBooks on EBSCOhost
Keywords: American poetry -- 21st century; POETRY -- American -- General; LITERARY CRITICISM -- Poetry; POETRY -- General; American poetry; 2000-2099